PENGARUH INTELLECTUAL CAPITAL PERFORMANCE TERHADAP INTENSITAS PELAPORAN MODAL INTELEKTUAL - Harisnawati, Riska; Ulum, Ihyaul; Syam, Dhaniel (Jurnal Reviu Akuntansi dan Keuangan)
A b s tr a c tThe annual report as one of disclosure information made by a company. Purpose of this study toanalyze the effect of intellectual capital reporting performance to the intensity of intellectualcapital. Sample of this study are that the Islamic banking registered at Bank Indonesia inperiod 2011 to 2015. Samples were selected using purposive sampling method and obtained 24Islamic banking which is 9 for Islamic Banks and 15 for Islamic business unit. The analysis toolused is WarpPLS 3.0 with assessing inner and outer models prior models to test data analysisis feasible or not. Results of this study indicate that intellectual capital performance significantpositive effect on the intensity of intellectual capital reporting.Keywords: Intellectual Capital Performance, Intellectual Capital